Improved piezoelectric properties of lead-free (1-x)(Na-0.K-5(0.5))NbO3-x (Ba0.95Sr0.05)TiO3 ceramics by particle size control - Ha, Jong-Yoon; Choi, Ji-Won (ELSEVIER SCI LTD, 2014)
Lead-free piezoelectric (1-x)(Na0.5K0.5)NbO3-x(Ba0.93Sr0.05)TiO3 (NKN-BST) ceramics were prepared following a convention solid-state method using attrition milled powders. NKN BST systems formed homogeneous structures and the morphotropic phase boundary between orthorhombic and tetragonal phases was found to be 0.03 <= x <= 0.05. As the amount of BST was increased, the grain size of the NKN-BST system slightly decreased. The average grain size of NKN BST ceramics was in the range of 3-5 mu m, which is attributed to the small particle size and BST contents having high sintering temperatures. Not only was the surface morphology influenced by BST substitution, but also the piezoelectric properties, such as the Curie temperature and the piezoelectric constant, were modified. 0.95(Na0.5K0.5)NbO3-x(Ba0.93Sr0.05)TiO3 sintered at 1060 degrees C showed the best piezoelectric properties of epsilon(T)(3)/epsilon(0) = 1230, k(p)=39%, and d(33)=213 pC/N. (C) 2014 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: ELECTRICAL-PROPERTIES